1994
DOI: 10.1172/jci117427
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of growth hormone and insulin-like growth factor I on substrate oxidation and on insulin sensitivity in growth hormone-deficient humans.

Abstract: Insulin-like growth factor-I (IGF-I) is considered to be the mediator of the growth-promoting effects of growth hormone (GH). The metabolic effects of these two hormones, however, are different. Whereas GH treatment leads to elevated insulin and glucose levels, reduced insulin sensitivity, and impaired glucose tolerance, IGF-I treatment leads to reduced insulin and GH levels and enhanced insulin sensitivity. IGF-I may, therefore, not only be the mediator of the growth-promoting effects of GH but also a modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
72
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 39 publications
(57 reference statements)
7
72
2
1
Order By: Relevance
“…These changes included reduced circulating levels of leucine and leucine oxidation and the increased leucine MCR and net leucine balance. Similar findings have been observed after IGF-I administration in healthy subjects and GH-deficient adults (32)(33)(34)(35) and in patients with Cushing's syndrome after GH therapy (36). Evidence suggests that GH therapy results in upregulation of amino acid transporter systems (37), increasing the efficiency of cellular amino acid uptake.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These changes included reduced circulating levels of leucine and leucine oxidation and the increased leucine MCR and net leucine balance. Similar findings have been observed after IGF-I administration in healthy subjects and GH-deficient adults (32)(33)(34)(35) and in patients with Cushing's syndrome after GH therapy (36). Evidence suggests that GH therapy results in upregulation of amino acid transporter systems (37), increasing the efficiency of cellular amino acid uptake.…”
Section: Discussionsupporting
confidence: 64%
“…It is likely that decreased GH-mediated lipolysis and simultaneously enhanced insulin sensitivity resulted in the lower circulating NEFA levels during the IGF-I administration. A study of IGF-I administration in GH-deficient adults also demonstrated reductions in NEFA levels (33), indicating that IGF-I may also regulate NEFA levels through mechanisms independent of GH.…”
mentioning
confidence: 99%
“…Each value is the mean ± standard error of the mean. GH is thought to increase the basal metabolic rate through thermogenesis [14] and the induction of catecholamine release [28], increasing the conversion of the thyroid hormone T4 to the more metabolically active T3 [29], and increasing IGF-1 secretion, which may participate in increasing resting energy expenditure [30]. Conversely, adult KK-A y mice with markedly elevated IGF-1 levels showed decreased UCP1 and UCP3 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…The mean energy intake of the individuals in our study (E6213 kJ) was below that reported in a population-based study comprising the whole Brazilian population (EN-DEF ¼ National Study of Family Expenditure), a study carried out in 1974/1975, and in which the mean energy consumption was 8493 kJ (Fundação IBGE, 1977). More recently, another population-based study (Hussain et al, 1994) found even higher numbers (10 878 kJ). Obesity, stunting and food pattern T T Florêncio et al…”
Section: Stature and Energy Consumptionmentioning
confidence: 92%
“…For instance, the lower concentration of the insulin-like growth factor I (IGF-I) is accompanied by a lower sensitivity of the hormone sensitive lipase to the lipolytic hormones. For this reason, any reduction in IGF-I may result in lower fat oxidation (Hussain et al, 1994).…”
Section: Stature and Energy Consumptionmentioning
confidence: 99%